Direct Nucleophilic Substitution Reaction of Cage B−H Bonds by Grignard Reagents: A Route to Regioselective B4‐Alkylation of o‐Carboranes. Issue 30 (23rd May 2017) - Tang, Cen; Zhang, Jiji; Xie, Zuowei
Abstract: Direct nucleophilic substitution reaction of cage B−H bonds of o ‐carboranes by Grignard reagents in the absence of any transition metals has been achieved for the first time, and leads to the regioselective synthesis of a series of 4‐alkyl‐1, 2‐diaryl‐ o ‐carboranes in very high yields. The presence of two electron‐withdrawing aryl groups on the cage carbon atoms is crucial to realizing the reaction. The regioselectivity is controlled by both electronic and steric factors. This work represents a new strategy for the development of methods for carborane functionalization. Abstract : Rattled cage : The title reaction proceeds in the absence of transition metals and leads to 4‐alkyl‐1, 2‐diaryl‐ o ‐carboranes in high yields. The presence of two electron‐withdrawing aryl groups on the cage carbon atoms is crucial for the reaction, and the regioselectivity is controlled by both electronic and steric factors.